2019
DOI: 10.1098/rspb.2019.0297
|View full text |Cite
|
Sign up to set email alerts
|

The decision to move: response times, neuronal circuits and sensory memory in a simple vertebrate

Abstract: All animals use sensory systems to monitor external events and have to decide whether to move. Response times are long and variable compared to reflexes, and fast escape movements. The complexity of adult vertebrate brains makes it difficult to trace the neuronal circuits underlying basic decisions to move. To simplify the problem, we investigate the nervous system and responses of hatchling frog tadpoles which swim when their skin is stimulated. Studying the neuron-by-neuron pathway from sensory to hindbrain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…We also tested interfering with development at the later blastula stage (>64 cells) by a similar protocol. While subsequent morphological development was normal under lit and dark conditions (Fig S9b-c), sensorimotor responses to mechanical stimulation 48 were suppressed by lit SBTubA4P only (Fig S9e, Movie S12). Interestingly, the tubulin-inhibiting azobenzene photoswitch PST-1P (Fig S9e ) light-independently suppresses sensorimotor responses.…”
Section: Sbtub Photocontrol In Live Animals Enables Targeted Blockadementioning
confidence: 99%
“…We also tested interfering with development at the later blastula stage (>64 cells) by a similar protocol. While subsequent morphological development was normal under lit and dark conditions (Fig S9b-c), sensorimotor responses to mechanical stimulation 48 were suppressed by lit SBTubA4P only (Fig S9e, Movie S12). Interestingly, the tubulin-inhibiting azobenzene photoswitch PST-1P (Fig S9e ) light-independently suppresses sensorimotor responses.…”
Section: Sbtub Photocontrol In Live Animals Enables Targeted Blockadementioning
confidence: 99%
“…It has been shown that the hatchling Xenopus laevis tadpole responds to trunk skin stimuli by initiating swimming with a delay of 50-150ms (26)(27)(28). We demonstrated that this long and variable delay resembles the accumulation of excitation proposed for complex brain circuits active during motor decision-making (29,30), in contrast to quick reflexes (e.g the quick C-start response; (31)), thus concluding that sensory processing and motor decision mechanisms are present even at this early developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…The sensory (Rohon-Beard cells, RB) and sensory pathway neurons (dorsolateral ascending and dorsolateral commissural neurons, dla and dlc, respectively), which transmit the sensory information from the periphery to the tadpole's brain, are very well-known (19,20). Their firing, early in response to stimulation, cannot explain neither the variability, nor the delay detected in dINs' firing latencies and swim initiation (27). Indeed, the variable and long process of accumulation of excitation recorded in dINs could be mimicked through modelling only by inserting an excitatory recurrent network within the brainstem sensory pathway (26).…”
Section: Introductionmentioning
confidence: 99%
“…Frog tadpoles, one of the most numerous vertebrate animals on earth, are simple, vulnerable animals that rely on swimming to escape from predators. The simplicity of the hatchling Xenopus tadpole and its nervous system presents a rare opportunity for experimental and computational studies (Roberts et al, 2014; Roberts et al, 2010b) where detailed information is available on behaviour, sensory systems, the central nervous system ( CNS ) (Roberts et al, 2019), body components and their properties as well as body-water interaction (Hoff and Wassersug, 2000).…”
Section: Introductionmentioning
confidence: 99%